2007
DOI: 10.1007/s11099-007-0071-8
|View full text |Cite
|
Sign up to set email alerts
|

Photoinhibition of photosynthesis in water deficit leaves of grapevine (Vitis vinifera L.) plants

Abstract: Photoinhibition under irradiance of 2 000 µmol m -2 s -1 (HI) was studied in detached control (C) and water deficit (WD) leaves of grapevine (Vitis vinifera L.) plants. The degree of photoinhibition was determined by means of the ratio of variable to maximum chlorophyll (Chl) fluorescence (F v /F m ) and electron transport measurements. The potential efficiency of photosystem (PS) 2, F v /F m , marginally declined under HI in WD-leaves without significant increase of F 0 . In contrast, F v /F m ratio declined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…However, subjecting plants to water stress at flowering stage caused the highest reduction in all growth parameters in the two seasons. The adverse effect of drought stress on growth roselle parameter may be attributed to the decrease in net photosynthetic rates (photo inhibition) in Plants due to stomatal closure, which decreases or prevents water loss but reduces CO 2 availability for chloroplast , Bertamini, et al (2007). These results were agreed with those reported by El-Boraie et al (2009) on roselle plant.…”
Section: Resultssupporting
confidence: 90%
“…However, subjecting plants to water stress at flowering stage caused the highest reduction in all growth parameters in the two seasons. The adverse effect of drought stress on growth roselle parameter may be attributed to the decrease in net photosynthetic rates (photo inhibition) in Plants due to stomatal closure, which decreases or prevents water loss but reduces CO 2 availability for chloroplast , Bertamini, et al (2007). These results were agreed with those reported by El-Boraie et al (2009) on roselle plant.…”
Section: Resultssupporting
confidence: 90%
“…The F v /F m in drought-treated leaves of Kelleris 16 was 0.38, which is much below the considered boundary value (0.75) for fully functional PSII (BOLHÁR-NORDENKAMPF et al 1989). A reduction of F v /F m in drought stress was reported by many authors (BAUERLE et al 2003, BERTAMINI et al 2007). Performance index (PI ABS ) was decreased in drought-treated leaves of both investigated genotypes (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Some authors report that shading has little effect on berry ripening and sugar accumulation but increases the pH and titratable acidity of the must (Ristic et al, 2007 ;Matus et al, 2009). Others have found that shaded berries ripen later and have a lower total soluble content (Bertamini et al, 2007 ;Marta et al, 2008 ;Abd El-Razek et al, 2010). Greer and Weedon (2012) found that irradiance, irrespective of seasonal temperatures, has no effect on the timing of budbreak nor on shoot phenology, stem growth or yield.…”
Section: Introductionmentioning
confidence: 99%